2020
DOI: 10.1038/s41559-020-01288-w
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of marine giant viruses reveals their interplay with eukaryotes and ecological functions

Abstract: Nucleocytoplasmic large DNA viruses (NCLDVs) are ubiquitous in marine environments and infect diverse eukaryotes. However, little is known about their biogeography and ecology in the ocean. By leveraging the Tara Oceans pole-to-pole metagenomic data set, we investigated the distribution of NCLDVs across size fractions, depths and biomes, as well as their associations with eukaryotic communities. Our analyses revealed a heterogeneous distribution of NCLDVs across oceans, with an elevated uniqueness in polar bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
97
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 73 publications
21
97
2
Order By: Relevance
“…This was expected given the high abundance and diversity of NCLDVs in marine environments (18,21) and the identification of HGT between these viruses and diverse eukaryotic lineages (24). The networks were dominated by the Mimiviridae nodes, which is consistent with previous reports that Mimiviridae is the most abundant and has the widest array of transcribed genes out of NCLDV families in marine environments (22,23). Mimiviridae was known to infect amoebae, algae, and stramenopiles (3).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This was expected given the high abundance and diversity of NCLDVs in marine environments (18,21) and the identification of HGT between these viruses and diverse eukaryotic lineages (24). The networks were dominated by the Mimiviridae nodes, which is consistent with previous reports that Mimiviridae is the most abundant and has the widest array of transcribed genes out of NCLDV families in marine environments (22,23). Mimiviridae was known to infect amoebae, algae, and stramenopiles (3).…”
Section: Discussionsupporting
confidence: 85%
“…Type B DNA polymerase (polB) was used as the marker gene for NCLDVs. A total of 6818 NCLDV polB OTUs were extracted from the metagenomic datasets (i.e., the second version of the Ocean Microbial Reference Gene Catalog, OM-RGC.v2) using the pplacer phylogenetic placement method (ML tree) (22,60,61). These polB sequences were classified into seven NCLDV families (Mimiviridae, Phycodnaviridae, Marseilleviridae, Ascoviridae, Iridoviridae, Asfarviridae, and Poxviridae) and two other giant virus groups ("Medusaviridae" and "Pithoviridae").…”
Section: Metagenomic and Metabarcoding Datamentioning
confidence: 99%
“…While most cultured Asfarviruses were isolated from sewage samples, various metagenomic studies have revealed that NCLDVs are highly diverse and abundant in aquatic environments (Monier et al, 2008; Hingamp et al, 2013), and one recent study noted that Asfarviruses are prevalent in some marine samples (Endo et al, 2020). To examine the biogeography of the Asfarvirus MAGs in more detail we conducted a fragment recruitment analysis using reads from the Tara oceans expedition (Sunagawa et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Some families of NCLDV such as the Poxviridae, Asfarviridae, Iridoviridae , and Phycodnaviridae have been studied for decades, while others, such as the Pandoraviridae, Mimiviridae, and Marseilleviridae, have been discovered relatively recently (Raoult et al, 2004; Boyer et al, 2009; Philippe et al, 2013; Abergel et al, 2015). Although amoebae have been used as an effective system to cultivate many recently-discovered NCLDV, recent cultivation-independent studies have discovered a wide range of these viruses in diverse environments, suggesting that uncultivated members of this viral phylum are ubiquitous in the biosphere (Monier et al, 2008; Hingamp et al, 2013; Bäckström et al, 2019; Endo et al, 2020; Moniruzzaman et al, 2020a; Schulz et al, 2020). Given the notable complexity of NCLDVs and their cosmopolitan distribution, there is a need to better understand their genomic diversity and biogeography.…”
Section: Introductionmentioning
confidence: 99%
“…The family Mimiviridae is a major group of large DNA viruses that infect diverse eukaryotes in marine environments (31). A recent study revealed an association between eukaryote communities and Mimiviridae in a global metagenomic dataset (32). Another study detected cooccurring pairs of eukaryotes and large DNA viruses including members of the Mimiviridae through time-series sampling for more than 1 year in Northern Skagerrak, South Norway (18).…”
Section: Introductionmentioning
confidence: 99%